Linguistics of Leisure: A Systemic Functional Study of Tourism Opinion Discourse in Indonesia - Sugiarti, Rara; Santosa, Riyadi; Wiratno, Tri; Djatmika; Wibowo, Agus Hari; Arkida, Teisar (Langkawi: Journal of The Association for Arabic and English, 2026)
This study investigates the strategic deployment of appraisal system resources in Indonesian tourism opinion discourse, comparing evaluative patterns in articles focusing on Java versus those on destinations outside Java, across Detik.com, Kompasiana.com, and Jawapos.com. The research problem addresses the language choices used to construct diverse tourist destinations in an expanding digital sphere. Employing a qualitative descriptive approach grounded in Systemic Functional Linguistics and Appraisal Theory, the study analyzes six tourism opinion articles, purposively selected from the three prominent online media outlets. Findings indicate that Java destinations are presented with a multifaceted image, balancing positive APPRECIATION attributes like affordability, accessibility, and comfort, with more frequent negative JUDGMENT regarding site challenges and visitor responsibility. On the other hand, non-Java destinations are framed as exceptional and aspirational through highly intensified positive evaluations and prominent APPRECIATION:QUALITY and APPRECIATION:VALUATION, reflecting a strategy to differentiate and highlight unique selling propositions for less familiar audiences. While all the articles are MONOGLOSSIC, media variations further reveal distinct editorial practices, with Kompasiana emphasizing JUDGMENT for responsible tourism and Jawa Pos using hyperbole GRADUATION for aspirational non-Java travel, while Detik maintains a more HETEROGLOSSIC informational tone. This research contributes to understanding how language systematically persuades in digital tourism promotion, offering insights for academics and practitioners on effective audience engagement and destination branding in Indonesia.